Study of Trifolium angulatum (Waldst. et. Kit.) phytomass in Karcag - Varga, Krisztina; Bojté, Csilla; Csízi, István; Halász, András; Nagy, Dominik (JOURNAL OF LANDSCAPE ECOLOGY, 2024)
Our studies were conducted at the Hungarian University of Agricultural and Life Sciences in Karcag, where in 2023, due to favourable precipitation and temperature conditions, we had the opportunity to study the phytomass yields of a massively reproducing annual Trifolium species in a saline soil condition. Yield measurements (green yield, hay yield, crude protein yield, dry matter yield) showed that in all cases higher yields were measured in the Trifolium angulatum-covered grassland than in the control grassland, and statistical analysis showed a close correlation in all cases. Through our studies, we aimed to provide new data on the specific floristic events in environmentally managed grassland in the Pannonian Basin from a farmer's perspective
Keywords: short-lived clover; extensive grassland; green yield; dry matter yield; protein